Introduction - Hyde, W.F.; Jintao Xu; Belcher, B. (Resources for the Future and Center for International Forestry Research, 2003)
This book is about the impacts of China's reforms on the forestry sector of its economy. This chapter introduces the objective of this book which is to examine the experience of China's forestry sector with respect to the full set of forest and nonforest policy reforms introduced since 1978 and followed by a summary of the changes affecting China's forests since 1978, a synopsis of China's forest administration and its geographic organization, and a chronology of China's general reforms and their broad effects. The introductory chapter closes with a review of specific forestry-sector reforms and an introduction to the analytical chapters that follow.